Exhaustive Search of Large-scale Crowd-starting Schemes Using Hierarchical Iterative Grid Search Method - Nishikawa, Noriaki (Transaction of the Japan Society for Simulation Technology, 2024)
In order to alleviate congestion at the start of large-scale marathons and walking events, efforts are being made on a trial basis to adopt a wave start, in which participants form groups and start in a series of waves, instead of the conventional mass start. In this paper, we conducted an exhaustive search for a crowd-starting scheme that maximizes the event satisfaction felt by participants in a large-scale walking event by using complementary microscopic and macroscopic models that describe the behavior of pedestrians. As a result, we quantitatively clarified how the wave arrangement and the time gap between the start of each wave should be in a wave start.